Imbalanced Activation of Wnt-/β-Catenin-Signaling in Liver Endothelium Alters Normal Sinusoidal Differentiation - Koch, Philipp-Sebastian; Sandorski, Kajetan; Heil, Joschka; Schmid, Christian D.; Kürschner, Sina W.; Hoffmann, Johannes; Winkler, Manuel; Staniczek, Theresa; de la Torre, Carolina; Sticht, Carsten; Schledzewski, Kai; Taketo, Makoto Mark; et al. (Frontiers in Physiology, 2021)
Endothelial Wnt-/β-catenin signaling is a key regulator of the tightly sealed blood-brain barrier. In the hepatic vascular niche angiokine-mediated Wnt signaling was recently identified as an important regulator of hepatocyte function including determination of final adult liver size, liver regeneration and metabolic liver zonation. Within the hepatic vasculature, liver sinusoidal endothelial cells (LSEC) are morphologically unique and functionally specialized micro¬vascular endothelial cells (EC). Pathological changes of LSEC are involved in chronic liver diseases, hepatocarcino¬genesis and liver metastasis. To comprehensively analyze the effects of endothelial Wnt-/β-catenin signaling in the liver, we used endothelial subtype-specific Clec4g-iCre mice to generate hepatic endothelial cells with overexpression of Ctnnb1. In the resultant Clec4g-iCretg/wt;Ctnnb1(Ex3)fl/wt (Ctnnb1OE-EC) mice, activation of endothelial Wnt-/β-catenin signaling resulted in sinusoidal transdifferentiation with disturbed endothelial zonation, i.e. loss of midzonal LSEC marker Lyve1 and enrichment of continuous EC genes such as CD34 and Apln. Notably, gene set enrichment analysis revealed overrepresentation of brain endothelial transcripts. Activation of endothelial Wnt-/β-catenin signaling did not induce liver fibrosis or alter metabolic liver zonation, but Ctnnb1OE-EC mice exhibited significantly increased plasma triglyceride concentrations, while liver lipid content was slightly reduced. Ctnnb1 overexpression in arterial EC of the heart has been reported previously to cause cardiomyopathy. As Clec4g-iCre is active in a subset of cardiac EC, it was not unexpected that Ctnnb1OE-EC mice showed reduced overall survival and cardiac dysfunction. Altogether, balanced endothelial Wnt-/β-catenin signaling in the liver is required for normal LSEC differentiation and for maintenance of normal plasma triglyceride levels.